Investments Decision Making In The Covid-19 Pandemic: Sharia Stock Valuation Model - Nofrianto (Institute of Computer Science (IOCS), 2021)
This study aims to find the intrinsic value of the stock prices of sharia companies listed in the Jakarta Islamic Index (JII) before and during the pandemic. Explaining the intrinsic value of stocks helps make the right investment decisions, especially during this period. One way to calculate the intrinsic value of stocks is using fundamental analysis with PER, DDM, and PBV. The sample of this study was 30 companies listed in JII. The sampling technique used in this study was purposive sampling. The data used are secondary. The research results with the PER method, before the pandemic, there were 18 companies, and 17 companies were experiencing undervalued during the pandemic. The second method with DDM, there were 27 companies before the pandemic, and during the pandemic, 25 companies were experiencing undervalued. In the third method with PBV, there were 22 companies before the pandemic, and 25 companies were experiencing undervalued during the pandemic. The most exact investment decision-making is to buy stocks that are undervalued (cheap). The most accurate valuation of stock prices is the DDM method which has the smallest RMSE value.